Evaluation of Selected Risk Factors in Third Party Liability Insurance Agreements for Motor Vehicle Owners - Celczyńska, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The aim of the study is to provide the evaluation of selected risk factors in third party liability insurance agreements for motor vehicle owners. The study covers: age admitted, the astrological sign of policy-holder and the age of vehicle.Automobile insurance risk is determined by a number of factors arising from both external environment as well as psychological features of policy-holders. The study was preliminary and may constitute the basis for further research.